Turnaround and Sustainability in Economic Crisis: The Case of NEXT PLC - Zhang, Biyan (2013)
Purpose- against a background of continued weak economic conditions and with many firms experiencing declining financial performance, this paper presents a synthesis of the business turnaround literature and combines with analysis case –NEXT plc. It purposes to discus the turnaround strategies can keep the declining firm sustainability recovery, during the economic cycle.